Perilaku Monopoli dalam Perdagangan Elektronik: Analisis Hukum Persaingan Usaha terhadap TikTok - Ayup Suran Ningsih; Harumsari Puspa Wardhani (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2026)
This article analyzes monopolistic behavior in electronic commerce conducted through Electronic Systems (Perdagangan Melalui Sistem Elektronik/PMSE) on the TikTok platform, particularly through the TikTok Shop feature, from the perspective of Indonesian competition law. The purpose of this study is to examine the compatibility of TikTok's social commerce business model with Law Number 5 of 1999 on the Prohibition of Monopoly Practices and Unfair Business Competition, as well as regulations governing PMSE. The research method employed is a normative juridical legal approach, focusing on a socio-legal perspective, which relies on secondary legal materials, including statutory regulations, legal doctrine, academic literature, relevant official reports, and empirical data. The results of this study indicate that integrating social media and e-commerce functions into a single digital ecosystem creates the significant potential for monopolistic practices, including control over content-distribution algorithms, dominance over user data, market access discrimination, and predatory pricing. This condition has the potential to harm fair business competition and suppress the sustainability of micro, small, and medium-sized enterprises (MSMEs). This study concludes that the existing legal framework for business competition has not been fully adaptable to the characteristics of platform-based digital businesses. Therefore, it is necessary to update the regulations framework and strengthen supervision by competition authorities so that the digital commerce ecosystem operates fairly, equitably, and sustainably.